Effects of 900 MHz electromagnetic field emitted by cellular phones on electrocardiograms of guinea pigs. (February 2014) - Meral, I; Tekintangac, Y; Demir, H
This study was carried out to determine the effects of electromagnetic field (EMF) emitted by cellular phones (CPs) on electrocardiograms (ECGs) of guinea pigs. A total of 30 healthy guinea pigs weighing 500–800 g were used. After 1 week of adaptation period, animals were randomly divided into two groups: control group ( n = 10) and EMF-exposed group ( n = 20). Control guinea pigs were housed in a separate room without exposing them to EMFs of CPs. Animals in second group were exposed to 890–915 MHz EMF (217 Hz of pulse rate, 2 W of maximum peak power and 0.95 wt kg −1 of specific absorption rate) for 12 h day −1 (11 h 45 min stand-by and 15 min speaking mode) for 30 days. ECGs of guinea pigs in both the groups were recorded by a direct writing electrocardiograph at the beginning and 10th, 20th and 30th days of the experiment. All ECGs were standardized at 1 mV = 10 mm and with a chart speed of 50 mm sec −1 . Leads I, II, III, lead augmented vector right (aVR), lead augmented vector left (aVL) and lead augmented vector foot (aVF) were recorded. The durations and amplitudes of waves on the trace were measured in lead II. The data were expressed as mean with SEM. It was found that 12 h day −1 EMF exposure for 30 days did not have any significant effects on ECG findings of guinea pigs. However, this issue needed to be further investigated in a variety of perspectives, such as longer duration of exposure to be able to elucidate the effects of mobile phone-induced EMFs on cardiovascular functions.